Teachers Utilization of Instructional Materials for Effective Teaching of Business Studies in Junior Secondary Schools in Delta State - Onajite, G. O.; Olaniyi, O. N.; Oyerinde, D. O.; Onyesom, Moses; Aina, M. A. (Mediterranean Journal of Social Sciences, 2019)
This study examined teachers’ utilization of instructional materials for effective teaching of business studies in junior secondary schools in Delta State. The study was guide by three research questions. The study employed the descriptive survey research design. Population for the study consisted of 665 business studies teachers in the 448 public junior secondary schools in Delta State. The proportionate stratified random sampling technique was used to select a sample size of 50% of 333 out from 665 business studies teachers from 224 public junior secondary schools in Delta State. A questionnaire titled: Teachers’ Utilization of Instructional Materials for Teaching Business Studies Questionnaire (TUIMTBSQ), containing 38 items was used in conducting the study. Both the validity and reliability of the research instrument were established. Data were analyzed using mean score at 2.50 rating and standard deviation. Findings of the study revealed among others that business studies teachers’ utilization of instructional materials such as printed and non-printed materials for effective teaching of the subject in junior secondary schools in Delta State was to a low extent, which was minimal. The study recommended among others that: State Government and State Education Board should support teachers’ utilization of printed and non-printed instructional materials in business studies through adequate funding and procurement of materials needed in teaching business studies in the junior secondary schools in Delta State. Principals should also improvise the required printed and non-printed instructional materials for business studies teachers in the school. This must be accorded with constant supervision and continuous staff training and retraining programmes that will improve teachers’ utilization of printed and non-printed technological devices that will aid effective teaching in the classroom.